Direct functionalization of cyclic ethers with maleimide iodides via free radial-mediated sp3 C–H activation. Issue 39 (15th April 2021) - Cheng, Xiaoyu; Li, Baojun; Zhang, Mengsi; Lu, Haotian; Wang, Wenbo; Ding, Yun; Hu, Aiguo
Abstract : A new C–C bond formation reaction was developed through free radical-initiated direct C–H activation of cyclic ethers with maleimide iodides under mild reaction conditions. Abstract : Cyclic ethers are important scaffolds employed in the synthesis of various natural products and pharmaceutical ingredients. A novel free radical-initiated reaction between cyclic ethers and maleimide iodides through C–H activation is developed, avoiding the use of transition metallic catalysts. This method provides a simple approach to derive cyclic ethers, which were further applied in various cross coupling reactions.